Current research of Assisted Reproductive Technology for women with early endometrial cancer and atypical endometrial hyperplasia after conservative treatment - Jiang, Yan-le; Lin, Yan-ying; Chen, Chen-xi; Li, Yu-xin; Xie, Huang-yan; Zheng, Bei-hong (Frontiers in Endocrinology, 2024)
As the incidence of endometrial cancer (EC) and atypical endometrial hyperplasia (AEH) has been increasing, and has shown young trend. It is crucial to study the fertility-preserving treatment of endometrial lesions and fertility-promoting protocols.Age, obesity, and irregular ovulation are not only high-risk factors for endometrial lesions but also key factors affecting female fertility. Assisted reproductive technology (ART) can significantly improve pregnancy outcomes in patients with AEH and EC after conservative treatment. Based on the existing studies, this article reviews the progress of research on pregnancy outcomes of ART and its influencing factors in such patients. It helps physicians in providing optimal fertility guidance.